Talking About Food: Using institutional stories to build equity within food system planning in Everett, MA. - Etingoff, Kimberly. (2017)
Abstract: This research introduces the concept of institutional storytelling into theory and practice. Institutional stories explain the origin and continuation of established organizational systems, and may be used by planners, policymakers, and other changemakers for justice and equity purposes. A case study of a food justice initiative in Everett, Massachusetts is presented as a way to examine institutional storytelling in practice. Three levels of actors are included in the case study--grassroots, local government, and state government--in order to synthesize narratives that illustrate a particular institution. The concept of institutional story draws on a framework including the existing and potential uses of storytelling in policy and planning, urban political ecology theory, the alternative food movement, and urban agriculture. The story of Everett Community Growers is used to determine the effectiveness of the use of institutional story within the case organization. Recommendations are developed for actors involved with Everett Community Growers, and for planners and policymakers interested in advancing equity and justice through institutional storytelling.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Lorlene Hoyt.; Keyword: Urban planning.